CONTRIBUTION OF ISLAMIC LAW IN REGIONAL REGULATION OF TANGERANG CITY NUMBER 8 OF 2005 CONCERNING PROHIBITION OF PROSTITUTION - Murofikoh, Dede Ika; Pamula, Fauzi Rahmat; Mariana, Mariana (Ilmu Hukum, Sharia and Law Faculty, Sunan Gunung Djati Islamic State University of Bandung, 2024)
Today the development of disobedience in people's lives is increasing and rampant. Disobedience is very varied, including theft, selling liquor, drugs, beheading, human trafficking to prostitution and adultery. Besides this, the Tangerang city government responded by issuing Regional Regulation No. 8 of 2005 concerning the prohibition of prostitution. The data used in this study is secondary data and the type of research is descriptive. The method used in this study is a normative juridical approach. Prostitution is an insult to human dignity, especially women. Therefore, the Qur'an and the hadith of the Prophet Muhammad, which are the main sources of Islamic law, both have forbidden adultery and prostitution.Dewasa ini perkembangan kemaksiatan dalam kehidupan masyarakat semakin meningkat dan merajalela. Kemaksiatan yang terjadi sangat beragam, mulai dari pencurian, menjual minuman keras, narkoba, pembegalan, perdagangan manusia hingga prostitusi dan perzinahan. Disamping itu, pemerintah kota Tangerang meresponnya dengan mengeluarkan Peraturan Daerah No. 8 tahun 2005 tentang larangan pelacuran. Data yang digunakan dalam penelitian ini adalah data sekunder dan jenis penelitiannya adalah deskriptif. Metode yang digunakan dalam penelitian ini adalah pendekatan yuridis normatif. Pelacuran merupakan suatu penghinaan terhadap martabat manusia, khususnya perempuan. Oleh karena itu, Al-Qur'an dan hadis Nabi Muhammad SAW yang merupakan sumber utama hukum Islam, keduanya telah mengharamkan perzinahan dan pelacuran.